Picky eating in children: causes and consequences - Taylor, Caroline M.; Emmett, Pauline M. (Proceedings of the Nutrition Society, 2019)
Picky eating is a common behaviour in early childhood. There is neither a universally accepted definition of picky eating, nor is there agreement on the best tool to identify it. Causes of picky eating include early feeding difficulties, late introduction of lumpy foods at weaning, pressure to eat and early choosiness, especially if the mother is worried by this; protective factors include the provision of fresh foods and eating the same meal as the child. The consequences for the child's diet include poor dietary variety and a possible distortion of nutrient intakes, with low intakes of iron and zinc (associated with low intakes of meat, and fruit and vegetables) being of particular concern. Low intakes of dietary fibre, as a result of low intakes of fruit and vegetables, are associated with constipation in picky eaters. There may be developmental difficulties in some children with persistent picky eating. There is little evidence, however, for a consistent effect of being a picky eater on growth trajectories. There may be a small subgroup of children in whom picky eating does not resolve who might be at risk of thinness during adolescence, or of developing an eating disorder or adult picky eating: these children need to be identified at an early age to enable support, monitoring and advice to be offered to parents. Strategies for avoiding or ameliorating picky eating include repeated exposures to unfamiliar foods, parental modelling of eating fruit and vegetables and unfamiliar foods, and the creation of positive social experiences around mealtimes.